2021
DOI: 10.1513/annalsats.202008-913oc
|View full text |Cite
|
Sign up to set email alerts
|

Association between Leflunomide and Pulmonary Hypertension

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…For example, several experiments failed to reproduce PAH with well identified drugs such as aminorex or fenfluramine 28,29 . Nevertheless, these experiments, sometimes complemented by the use of human tissue samples from PAH patients and human primary cells, are indispensable to understand the mechanisms of drug provoked PAH and have proven their importance in the exploration of recent signals of PAH, such as with dasatinib or leflunomide 24,30,31 …”
Section: Discussionmentioning
confidence: 99%
“…For example, several experiments failed to reproduce PAH with well identified drugs such as aminorex or fenfluramine 28,29 . Nevertheless, these experiments, sometimes complemented by the use of human tissue samples from PAH patients and human primary cells, are indispensable to understand the mechanisms of drug provoked PAH and have proven their importance in the exploration of recent signals of PAH, such as with dasatinib or leflunomide 24,30,31 …”
Section: Discussionmentioning
confidence: 99%
“…However, similar to dasatinib-induced PAH, there were patients with persistent PAH despite permanent discontinuation of the offending medication. On the other hand, leflunomide is an immune modulator commonly used in multiple myeloma treatment regimens [11]. There have been reports of leflunomide being associated with PAH, but a recent series found pulmonary hypertension associated with leflunomide was rare and more common in patients with other PH risk factors.…”
Section: Medication-induced Pahmentioning
confidence: 99%
“…There have been reports of leflunomide being associated with PAH, but a recent series found pulmonary hypertension associated with leflunomide was rare and more common in patients with other PH risk factors. 11 Recently published European Society of Cardiology guidelines on cardio-oncology recommend baseline echocardiography before starting therapy with proteasome inhibitors (carfilzomib) or dasatinib [13].…”
Section: Medication-induced Pahmentioning
confidence: 99%
“…We also confirmed that high dose of mdivi-1 induced cellular senescence in VSMC treated with ox-LDL ( 151 ). In addition, mitochondrial fusion activator leflunomide used for the treatment rheumatoid arthritis has an adverse effect on humans, resulting in development of pulmonary hypertension ( 178 ).…”
Section: Perspectivementioning
confidence: 99%